Factors affecting pollination and pollinators in oil palm plantations: a review with an emphasis on the elaeidobius kamerunicus weevil (coleoptera: curculionidae) - King, Patricia Jie Hung (MDPI, 2023)
Pollination is crucial for oil palm yield, and its efficiency is influenced by multiple factors, including the effectiveness of Elaeidobius kamerunicus weevils as pollinators in Southeast Asia. Weevils transfer pollen between male and female flowers, leading to successful fertilization and fruit development, which contributes to higher oil palm yields and increased production of valuable oil. Understanding and conserving the weevil population is important for sustainable oil palm cultivation practices. The interaction between pollinators, including weevils, and environmental factors is complex, involving aspects such as pollinator behavior, abundance, diversity, and effectiveness, which are influenced by weather, landscape composition, and pesticide use. Understanding these interactions is critical for promoting sustainable pollination practices, including effective pest management and maintaining optimal pollinator populations. This review discusses various abiotic and biotic factors that affect pollination and pollinators in oil palm plantations, with a particular focus on weevils as primary pollinators. Factors such as rainfall, humidity, oil palm species, temperature, endogamy, parasitic nematodes, insecticides, predators, and proximity to natural forests can impact the weevil population. Further research is recommended to fill knowledge gaps and promote sustainable pollination practices in the oil palm industry.